Polyimide film adhesive tape and preparation process thereof

By adopting the secondary coating method of temperature step-up in the preparation process of polyimide film tape, the problems of difficult coating and poor adhesion are solved, the layer thickness and adhesion are significantly improved, and the waterproof and insulation performance of electromagnetic wires are improved.

CN119684916AActive Publication Date: 2025-03-25TIANJIN TIANYUAN ELECTRONICS MATERIAL
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510199181.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-24
Publication Date
2025-03-25
Estimated Expiration
2045-02-24

AI Technical Summary

Technical Problem

During the coating process, the surface tension of the polyimide film tape is low, the emulsion has a small solid content and high moisture content, which makes it difficult to apply, the layer thickness is difficult to increase, and the adhesion is poor, which affects the service life and stability of the motor.

Method used

The secondary coating is performed by the temperature step-up method. First, the polymer emulsion is melted and applied once, and then the secondary coating is performed and the high-temperature melt is performed to increase the thickness of the polymer emulsion layer to more than 15um.

Benefits of technology

It significantly improves the adhesion force of the polyimide film tape and its firmness with the electromagnetic wire, improves the performance of the wrapped electromagnetic wire, and achieves excellent electromagnetic wire waterproofing and electrical insulation effects.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of film adhesive tapes, and particularly discloses a polyimide film adhesive tape and a preparation process thereof. The preparation process of the polyimide film adhesive tape comprises the following steps: S1, preparing a polyimide film, and S2, coating a polymer emulsion: coating twice to finally obtain the polyimide film adhesive tape. According to the preparation process, the difficulty of coating the emulsion is low, the polymer emulsion layer is easy to thicken, the layer thickness of the polymer emulsion of the prepared polyimide film adhesive tape is not less than 15 microns, the bonding effect between the polyimide film adhesive tape and the electromagnetic wire is better, and the polyimide film adhesive tape can achieve more excellent waterproof and electrical insulation effects of the electromagnetic wire after wrapping.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of film tapes, and in particular to a polyimide film tape and a preparation process thereof. Background Art

[0002] Polyimide has unique physical and chemical properties and is widely used in many fields. In particular, it can be made into polyimide film tape, which can be used as the main raw material for the protective layer in the electromagnetic wire winding of large motor coil insulation. It has the advantages of good electrical insulation performance, thermodynamic stability and chemical stability, providing extremely high reliability for the operation of power equipment. This material is not only highly stable, but also can withstand the test of extreme environmental conditions, allowing the motor to operate stably in harsh environments such as high temperature, high humidity and high pressure.

[0003] The preparation process of polyimide film can be summarized as follows: first, dianhydride and diamine react in a polar solvent to form a precursor polyamic acid, then the polyamic acid solution is cast into a film, stretched, and imidized to finally obtain a polyimide film; and polyimide film tape is a tape obtained by coating a layer of polymer emulsion on the surface of the polyimide film and then drying it. During the coating process, the coating temperature must be maintained in the range of 310-400°C to make the emulsion flowable and easy to coat. The surface of polyimide film tape is very dry at room temperature, but it will melt after high temperature heating and thermally solidify with the electromagnetic wire to be coated, thereby sealing the electromagnetic wire and allowing the motor to operate normally in harsh environments such as high temperature and high humidity.

[0004] However, there are some problems in the coating process of polyimide film. Its surface tension is low. At the same time, the emulsions currently used are polyperfluoroethylene propylene emulsion and modified polytetrafluoroethylene emulsion, which have low solid content and high water content. This makes it difficult to coat the emulsion. It is difficult to apply a thick emulsion layer, and the emulsion cannot be coated a second time after one coating. Generally, the thickness does not exceed 10um, which will cause the adhesion between the polyimide film tape and the electromagnetic wire to be relatively poor. After wrapping, the waterproof, electrical insulation and other properties of the electromagnetic wire are damaged, which greatly affects the service life and stability of the motor. Summary of the invention

[0005] In order to solve the above technical problems, the present application provides a polyimide film tape and a preparation process thereof.

[0006] In a first aspect, the present application provides a process for preparing a polyimide film tape, comprising the following steps: S1, preparing a polyimide film, wherein the step of preparing the polyimide film comprises the step of preparing a polyamic acid polymer by reacting a diamine and a dibasic anhydride, S2, coating a polymer emulsion on the polyimide film; in the step S2, coating is performed twice, specifically: firstly, the temperature is raised to the melting temperature of the polymer in the polymer emulsion, coating is performed once, and drying is performed to obtain a surface roughness R a The invention discloses a layer of coated tape with a thickness of >1.45, followed by secondary coating, after which the temperature is raised by 40-50°C for melting, and finally cooled to set and dried to obtain a polyimide film tape; the polymer emulsion is one or both of polyperfluoroethylene propylene emulsion and modified polytetrafluoroethylene emulsion.

[0007] The specific operation of step S1 is: dissolving the diamine in N,N-dimethylacetamide, stirring under nitrogen protection until the diamine is completely dissolved, adding dibasic anhydride in small amounts multiple times, reacting for 1 hour after each addition of dibasic anhydride, and the reaction temperature is 20°C. When the solid content in the system is greater than 15wt%, degassing treatment is performed to obtain a polyamic acid polymer, and then the prepared polyamic acid polymer is uniformly coated on the glass, and then sent to an environment with a temperature of 100°C and allowed to stand for 0.5h, transferred to an environment with a temperature of 150°C and allowed to stand for 0.5h, transferred to an environment with a temperature of 200°C and allowed to stand for 0.5h, transferred to an environment with a temperature of 250°C and allowed to stand for 0.5h , transferred to an environment with a temperature of 300°C and allowed to stand for 0.5h, and finally transferred to an environment with a temperature of 380°C and allowed to stand for 0.5h, taken out, and demolded in deionized water after the temperature drops to 25°C, and finally placed in an environment of 100°C and dried until the system has constant weight, and finally a polyimide film is obtained, wherein the weight ratio of diamine to dibasic anhydride is 25:27, and the number of times the dibasic anhydride is added can be flexibly selected according to the amount of materials used. The dibasic anhydride can be any one commonly used in the art. In the specific implementation manner of the present application, pyromellitic anhydride is used as an example for illustration. When gradually heating up, any commonly used equipment in the art, such as an oven, can be used, which can be flexibly adjusted according to different needs.

[0008] The coating in step S1 and the coating in step S2 may be performed by any commonly used equipment in the art. The specific implementation of the present application is described using a CNC coating machine as an example, and can be flexibly adjusted according to different needs.

[0009] The polymer emulsion in step S2 is any one of polyperfluoroethylene propylene emulsion or modified polytetrafluoroethylene emulsion. In the specific embodiment of the present application, modified polytetrafluoroethylene emulsion with lower solid content is used for illustration. The temperature during one coating is 350-360°C.

[0010] By adopting the above-mentioned technical scheme, in the polymer emulsion coating of step S2 of the present application, the coating temperature is first raised to a range that is basically the same as the polymer melting temperature of the polymer emulsion, so that the polymer emulsion is initially melted. At this time, the polymer emulsion will adhere to the polyimide film, and the surface is a relatively rough solid molten state. At this time, a second coating is performed. Since the surface roughness of the polymer emulsion after the first coating is relatively large, the second coating can still effectively increase the coating layer thickness of the polymer emulsion. After the second coating, a final high-temperature melting is performed to obtain a polyimide film tape with a polymer emulsion layer thickness of not less than 15um. In general, compared with the single coating in the existing preparation process of polyimide film tape, the present application increases the temperature in a step-by-step manner for secondary coating, which increases the thickness of the polymer emulsion layer by at least 5um and the adhesion by more than 4.8N / 10mm. In actual use, multiple coatings can be performed as needed until the final polymer emulsion layer thickness requirement is reached. During coating, it is only necessary to maintain the coating temperature the same as the first coating temperature. The specific implementation method of the present application takes secondary coating as an example because secondary coating can achieve a good polymer emulsion layer thickening effect.

[0011] In summary, the adhesion of the polyimide film tape prepared by the preparation process of the present application and its firmness with the electromagnetic wire are significantly improved, thereby improving its performance in wrapping the electromagnetic wire, and after wrapping, it can achieve excellent waterproofing and electrical insulation effects on the electromagnetic wire.

[0012] Preferably, before step S2, the polyimide film prepared in step S1 needs to be surface treated, and the specific steps are: completely immerse the polyimide film in an alkaline solution with a hydroxide ion concentration of 0.05-0.5 mol / L for alkaline treatment for 50-60 min, wash it with water, and then completely immerse it in an acid solution with a hydrogen ion concentration of 0.1-0.12 mol / L for acid treatment for 8-10 min, take it out, wash it with water, and dry it to obtain a surface-treated polyimide film.

[0013] Preferably, the hydroxide ion concentration of the alkaline solution is 0.2 mol / L.

[0014] By adopting the above technical solution, the present invention performs surface treatment on the polyimide film before coating the surface layer of the polymer emulsion, and immerses the polyimide film in an alkaline solution and an acid solution, thereby introducing a large number of hydrophilic groups into the molecules on the surface layer of the polyimide film, thereby significantly improving the surface roughness, surface tension and wettability of the polyimide film, and the dynamic water contact angle is not greater than 51.5°, and the surface roughness R aIt can reach 1.60, so the polyimide film after surface treatment can be fully wetted when coating the polymer emulsion, the difficulty of coating the emulsion is greatly reduced, and the thickness of the final polymer emulsion layer is greatly improved. Therefore, the surface treatment operation can significantly optimize the coating effect, so that the comprehensive performance of the polyimide film tape is improved, and the bonding effect with the electromagnetic wire is better. After wrapping, it can achieve better electromagnetic wire waterproofing and electrical insulation effects.

[0015] In the specific implementation of the present application, sodium hydroxide solution is used as the alkaline solution and hydrochloric acid solution is used as the acid solution for description, but this is only a feasible solution. In actual use, those skilled in the art can replace different types of alkaline solutions and acid solutions according to actual conditions.

[0016] In addition, the present application strictly controls the hydroxide ion concentration of the alkaline solution, thereby further optimizing the comprehensive performance of the polyimide film tape. If the hydroxide ion concentration is too high or too low, it will not have an effective surface treatment effect, and the surface roughness, surface tension and wettability of the polyimide film will not be improved enough. In addition, when the hydroxide ion concentration is too high, the surface layer of the polyimide film will be excessively corroded by the alkaline solution, thereby exposing a large number of internal structures. After this part of the internal structure comes into contact with the air, it will promote the initiation of cracks in the polyimide film tape, thereby damaging the tensile strength of the polyimide film. Experimental data show that when the hydroxide ion concentration of the alkaline solution is 0.2 mol / L, the dynamic water contact angle of the polyimide film is the smallest, only 42.1°, and the surface roughness R a It can reach 1.64, with remarkable coating ease, and the final emulsion layer thickness can reach 19.8um.

[0017] Preferably, the diamine comprises p-phenylenediamine, 4,4'-diaminodiphenyl ether and 4,4'-diaminobenzanilide in a weight ratio of 3:(3-4):(3-4).

[0018] After acid-base treatment, a small amount of cracks will appear on the surface of the polyimide film, and the tensile strength will be lost to a certain extent. However, the acid-base treatment will only reduce the tensile strength of the surface layer of the film. After testing, the tensile strength can still reach more than 150MPa at this time. However, in order to further improve the practicality of the polyimide film and further optimize its comprehensive performance, the present application also performs certain reinforcement treatments on it. By adopting the above-mentioned technical scheme, the present application adds a certain amount of 4,4'-diaminobenzanilide to the diamine system composed of p-phenylenediamine and 4,4'-diaminodiphenyl ether, partially replaces 4,4'-diaminodiphenyl ether, balances the ratio of rigid groups and flexible groups in the system, and makes the final polyimide film have higher tensile strength, which is more than 18% higher than the tensile strength of the film obtained when 4,4'-diaminobenzanilide is not added.

[0019] Preferably, in the step of preparing the polyamic acid polymer by reacting the diamine and the dibasic anhydride, a PDA-silane coupling agent-modified boron nitride is also added in an amount of 0.1-0.7wt% of the total amount of the dibasic anhydride and the diamine, specifically: the PDA-silane coupling agent-modified boron nitride is dispersed in N,N-dimethylacetamide, ultrasonically treated for 3-6h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then uniformly mixed with the diamine, and finally the dibasic anhydride is added to react, coated, and dried to obtain a polyimide film.

[0020] Preferably, the amount of the PDA-silane coupling agent modified boron nitride is 0.5 wt % of the total amount of dibasic anhydride and diamine.

[0021] Preferably, the PDA-silane coupling agent modified boron nitride is prepared by the following method: boron nitride is subjected to hydroxylation treatment, and then it is dispersed in anhydrous ethanol with a silane coupling agent, stirred for reaction, filtered, washed, and dried to obtain silane coupling agent modified boron nitride, and then the silane coupling agent modified boron nitride, dopamine and tromethamine are dispersed in an ethanol aqueous solution, the pH is adjusted to 8.4-8.6, stirred at 75-85°C for 5.5-6h, filtered, washed until the filtrate is colorless and neutral, and the solid obtained at this time is dried and ground to obtain PDA-silane coupling agent modified boron nitride.

[0022] Among them, the specific operation in the preparation method of PDA-silane coupling agent modified boron nitride is: first, 5 mol / L sodium hydroxide solution and nano-scale boron nitride are evenly mixed in a weight ratio of 10:1, and magnetically stirred at 80°C for 48 hours, and the solution is filtered and washed with deionized water until the filtrate is neutral, and then the filtered product is placed in a constant temperature drying oven at 120°C and dried for 24 hours to obtain hydroxylated boron nitride, and then a silane coupling agent is added to a water bath at 60°C, stirred to fully hydrolyze it, and the hydroxylated boron nitride is dispersed in the above solution, and then stirred at a temperature of 60°C. 3h, filtered and washed, dried at 90°C for 12h to obtain silane coupling agent modified boron nitride, wherein the amount of silane coupling agent is 2wt% of the total amount of hydroxylated boron nitride, and then the silane coupling agent modified boron nitride, dopamine and tromethamine in a weight ratio of 4:0.8:1.2 are dispersed in 50wt% ethanol aqueous solution, the pH is adjusted to 8.4-8.6, stirred at 75-85°C for 5.5-6h, filtered and washed until the filtrate is colorless and neutral, the solid obtained at this time is taken, dried at 60°C for 24h, and ground to obtain PDA-silane coupling agent modified boron nitride.

[0023] By adopting the above technical scheme, the present application first uses a strong base to hydroxylate the surface of nano-scale boron nitride, and then uses the reaction between this part of the hydroxyl group and the silane coupling agent to graft the silane coupling agent to the surface of the boron nitride, and then uses the polymerization reaction of dopamine in an aqueous solution with pH=8.4-8.6 to form a PDA (polydopamine) layer on the surface of the boron nitride. The PDA layer and the silane coupling agent can greatly enhance the interfacial adhesion strength between boron nitride and the diamine and dianhydride system and its dispersibility in the system.

[0024] Then, the present application adds PDA-silane coupling agent modified boron nitride with high interface adhesion strength and high dispersibility to the raw materials used for the polyimide film, and utilizes the excellent mechanical strength and chemical stability of boron nitride, supplemented by the sufficient dispersion and adhesion effect of PDA-silane coupling agent modified boron nitride, thereby significantly improving the overall tensile strength of the polyimide film. The final polyimide film has uniform internal components and high tensile strength, which is more than 15% higher than the tensile strength of the polyimide film without the addition of PDA-silane coupling agent modified boron nitride.

[0025] In addition, the application also strictly controls the amount of PDA-silane coupling agent modified boron nitride added to further optimize the mechanical properties of the polyimide film. If the amount added is too little, the reinforcement effect is insufficient. If the amount added is too large, although the PDA-silane coupling agent modified boron nitride will not form system defects and holes due to agglomeration, excessive addition will still cause a small part of the PDA-silane coupling agent modified boron nitride particles to inevitably aggregate, and will still promote cracks in the polyimide film after being stressed, resulting in a decrease in the mechanical properties of the film. It can be seen from the experimental data that when the amount of the PDA-silane coupling agent modified boron nitride is 0.5wt% of the total amount of dibasic anhydride and diamine, the tensile strength of the polyimide film is the highest, reaching 182.9MPa.

[0026] In a second aspect, the present application provides a polyimide film tape produced by the above-mentioned preparation process, wherein the layer thickness of the polymer emulsion of the polyimide film tape is not less than 15 um.

[0027] In summary, this application has the following beneficial technical effects: 1. The polyimide film of the present application has been surface treated during preparation, and a large number of hydrophilic groups are introduced into the molecules of the surface layer, which can be fully wetted when the polymer emulsion is coated, and the difficulty of coating the emulsion is greatly reduced. At the same time, the temperature is increased in a step-by-step manner during coating, so as to perform secondary coating and increase the thickness of the polymer emulsion layer to more than 15um. Therefore, the adhesion of the polyimide film tape of the present application and the firmness between the tape and the electromagnetic wire are significantly improved, thereby improving the performance of the tape wrapped around the electromagnetic wire, and after wrapping, it can achieve excellent waterproof and electrical insulation effects on the electromagnetic wire; 2. In the preparation process of the present application, the diamine in the polyimide film is prepared from p-phenylenediamine, 4,4'-diaminodiphenyl ether and 4,4'-diaminobenzanilide, which balances the ratio of rigid groups and flexible groups in the system, so that the final polyimide film has higher tensile strength, which is more than 18% higher than the tensile strength of the film obtained when 4,4'-diaminobenzanilide is not added; 3. The polyimide film of the present application also contains PDA-silane coupling agent modified boron nitride, which has good interface adhesion strength, dispersibility, excellent mechanical strength and chemical stability, and can significantly improve the overall tensile strength of the polyimide film. The tensile strength of the polyimide film is increased by more than 15% compared to the polyimide film without the addition of PDA-silane coupling agent modified boron nitride. DETAILED DESCRIPTION

[0028] Material Source Unless otherwise specified, the raw materials used in this application are all commercially available products, specifically: Boron nitride was purchased from Aladdin Biochemical Technology Co., Ltd., nanometer scale; Silane coupling agent was purchased from Shanghai Roen Reagent Co., Ltd., model KH-550; Dopamine was purchased from Aladdin Biochemical Technology Co., Ltd., CAS No. 62-31-7; Tromethamine was purchased from Aladdin Reagent Co., Ltd., CAS No. 77-86-1; p-Phenylenediamine was purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. and dried before use; 4,4'-Diaminodiphenyl ether was purchased from J&K Technology Co., Ltd. and dried before use; N,N-dimethylacetamide was purchased from Sinopharm Chemical Reagent Co., Ltd. and was distilled before use; Pyromellitic dianhydride was purchased from J&K Technology Co., Ltd. with a purity of 99%; Modified polytetrafluoroethylene emulsion was purchased from Dongguan Xinshengli Plastic New Material Technology Co., Ltd., with a solid content of 45wt%, CAS number 62-31-7; 4,4'-Diaminobenzanilide was purchased from J&K Technology Co., Ltd. and dried before use.

[0029] The present application is further described in detail below in combination with preparation examples, embodiments and comparative examples.

[0030] Preparation Example 1 The preparation method of PDA-silane coupling agent modified boron nitride comprises the following steps: 1 kg of 5 mol / L sodium hydroxide solution and 0.1 kg of nano-sized boron nitride were mixed evenly, and magnetically stirred at 80°C for 48 hours. The solution was filtered and washed with deionized water until the filtrate was neutral. The filtered product was then placed in a constant temperature drying oven at 120°C and dried for 24 hours to obtain hydroxylated boron nitride. 1 g of silane coupling agent was then added to a water bath at 60°C and stirred to fully hydrolyze it. 0.05 kg of hydroxylated boron nitride was dispersed in the above solution and heated at 60°C. The mixture was stirred for 3 h at room temperature, filtered and washed, and dried at 90 ° C for 12 h to obtain silane coupling agent modified boron nitride. Subsequently, 0.04 kg of silane coupling agent modified boron nitride, 8 g of dopamine and 12 g of tromethamine were dispersed in 8 kg of 50 wt% ethanol aqueous solution, the pH was adjusted to 8.4, stirred at 85 ° C for 6 h, filtered and washed until the filtrate was colorless and neutral. The solid obtained at this time was dried at 60 ° C for 24 h and ground to obtain PDA-silane coupling agent modified boron nitride.

[0031] Preparation Example 2 The preparation method of PDA-silane coupling agent modified boron nitride comprises the following steps: 1 kg of 5 mol / L sodium hydroxide solution and 0.1 kg of nano-sized boron nitride were mixed evenly, and magnetically stirred at 80°C for 48 h. The solution was filtered and washed with deionized water until the filtrate was neutral. The filtered product was then placed in a constant temperature drying oven at 120°C and dried for 24 h to obtain hydroxylated boron nitride. 1 g of silane coupling agent was then added to a 60°C water bath and stirred to fully hydrolyze it. 0.05 kg of hydroxylated boron nitride was dispersed in the above solution and heated at 60°C. The mixture was stirred for 3 h at 80 °C, filtered and washed, and dried at 90 °C for 12 h to obtain silane coupling agent modified boron nitride. Subsequently, 0.04 kg of silane coupling agent modified boron nitride, 8 g of dopamine and 12 g of tromethamine were dispersed in 8 kg of 50 wt% ethanol aqueous solution, the pH was adjusted to 8.8, stirred at 80 °C for 5.8 h, filtered and washed until the filtrate was colorless and neutral. The solid obtained at this time was dried at 60 °C for 24 h and ground to obtain PDA-silane coupling agent modified boron nitride.

[0032] Preparation Example 3 The preparation method of PDA-silane coupling agent modified boron nitride comprises the following steps: 1 kg of 5 mol / L sodium hydroxide solution and 0.1 kg of nano-sized boron nitride were mixed evenly, and magnetically stirred at 80°C for 48 h. The solution was filtered and washed with deionized water until the filtrate was neutral. The filtered product was then placed in a constant temperature drying oven at 120°C and dried for 24 h to obtain hydroxylated boron nitride. 1 g of silane coupling agent was then added to a 60°C water bath and stirred to fully hydrolyze it. 0.05 kg of hydroxylated boron nitride was dispersed in the above solution and heated at 60°C. The mixture was stirred for 3 h at 400 °C, filtered and washed, and dried at 90 °C for 12 h to obtain silane coupling agent modified boron nitride. Subsequently, 0.04 kg of silane coupling agent modified boron nitride, 8 g of dopamine and 12 g of tromethamine were dispersed in 8 kg of 50 wt% ethanol aqueous solution, the pH was adjusted to 8.6, stirred at 75 °C for 5.5 h, filtered and washed until the filtrate was colorless and neutral. The solid obtained at this time was dried at 60 °C for 24 h and ground to obtain PDA-silane coupling agent modified boron nitride.

[0033] Preparation Example 4 The preparation method of silane coupling agent modified boron nitride comprises the following steps: 1 kg of 5 mol / L sodium hydroxide solution and 0.1 kg of nano-sized boron nitride were mixed evenly, and magnetically stirred at 80°C for 48 hours. The solution was filtered and washed with deionized water until the filtrate was neutral. The filtered product was then placed in a constant temperature drying oven and dried at 120°C for 24 hours to obtain hydroxylated boron nitride. Subsequently, 1 g of silane coupling agent was added to a 60°C water bath and stirred to fully hydrolyze it. 0.05 kg of hydroxylated boron nitride was dispersed in the above solution, and stirring was continued at 60°C for 3 hours. The solution was filtered and washed, and dried at 90°C for 12 hours to obtain silane coupling agent-modified boron nitride.

[0034] Preparation Example 5 The preparation method of PDA-modified boron nitride comprises the following steps: Disperse 0.04 kg of nano-sized boron nitride, 8 g of dopamine and 12 g of tromethamine in 8 kg of 50 wt% ethanol aqueous solution, adjust pH to 8.6, stir at 75 ° C for 5.5 h, filter and wash until the filtrate is colorless and neutral. Dry the solid at 60 ° C for 24 h and grind to obtain PDA-modified boron nitride.

[0035] Example 1.1 A preparation process of a polyimide film tape comprises the following steps: S1. Preparation of polyimide film: 2.5 kg of diamine (1.25 kg of p-phenylenediamine and 1.25 kg of 4,4'-diaminodiphenyl ether) was dissolved in 50 L of N,N-dimethylacetamide. Under nitrogen protection, the diamine was stirred until it was completely dissolved. Pyromellitic anhydride was added in 9 times, 0.3 kg of pyromellitic anhydride was added each time. After each addition, the reaction was continued for 1 hour. The reaction temperature was 20°C. When the solid content in the system was greater than 15 wt%, a degassing treatment was performed to obtain a polyamic acid polymer. Subsequently, the prepared polyamic acid polymer was evenly coated on the glass using a CNC coating machine. The glass was then placed in an oven at 100°C for 0.5 hours and then transferred to a temperature oven. The film was placed in an oven at 150°C for 0.5h, transferred to an oven at 200°C for 0.5h, transferred to an oven at 250°C for 0.5h, transferred to an oven at 300°C for 0.5h, and finally transferred to an oven at 380°C for 0.5h. The film was taken out and placed in deionized water for demoulding after the temperature dropped to 25°C. The film was finally placed in an oven at 100°C for drying until the system had a constant weight. Finally, a polyimide film with a thickness of 25um and a surface roughness of R a is 1.27, and the dynamic water contact angle is 76.5°; S2, coating polymer emulsion: firstly, the temperature is raised to 350°C, and the surface of the polyimide film prepared in step S1 is coated with modified polytetrafluoroethylene emulsion by a CNC coating machine, and then dried to obtain a surface roughness R a A layer of coated tape with a g / L thickness of 1.46 is prepared, and then a modified polytetrafluoroethylene emulsion is coated for a second time using a CNC coating machine while the temperature remains unchanged. After coating, the temperature is increased to 400°C for melting, and after 3 hours, the tape is cooled and shaped, and dried to obtain a polyimide film tape.

[0036] Example 1.2 A preparation process of a polyimide film tape comprises the following steps: S1. Preparation of polyimide film: 2.5 kg of diamine (1.15 kg of p-phenylenediamine and 1.35 kg of 4,4'-diaminodiphenyl ether) was dissolved in 50 L of N,N-dimethylacetamide. Under nitrogen protection, the diamine was stirred until it was completely dissolved. Then, 0.3 kg of pyromellitic anhydride was added in 9 times. After each addition, the reaction was continued for 1 hour. The reaction temperature was 20°C. When the solid content in the system was greater than 15 wt%, a degassing treatment was performed to obtain a polyamic acid polymer. Subsequently, the prepared polyamic acid polymer was evenly coated on the glass using a CNC coating machine. Then, the glass was placed in an oven at 100°C for 0.5 hours and then transferred to a temperature oven. The film was placed in an oven at 150°C for 0.5h, transferred to an oven at 200°C for 0.5h, transferred to an oven at 250°C for 0.5h, transferred to an oven at 300°C for 0.5h, and finally transferred to an oven at 380°C for 0.5h. The film was taken out and placed in deionized water for demoulding after the temperature dropped to 25°C. The film was finally placed in an oven at 100°C for drying until the system had a constant weight. Finally, a polyimide film with a thickness of 25um and a surface roughness of R a is 1.26, and the dynamic water contact angle is 76.9°; S2, coating polymer emulsion: firstly, the temperature is raised to 355°C, and the surface of the polyimide film prepared in step S1 is coated with modified polytetrafluoroethylene emulsion by a CNC coating machine, and then dried to obtain a surface roughness R a A layer of coated tape with a g / L thickness of 1.46 is prepared, and then a modified polytetrafluoroethylene emulsion is coated for a second time using a CNC coating machine while the temperature remains unchanged. After coating, the temperature is increased to 400°C for melting, and after 3 hours, the tape is cooled and shaped, and dried to obtain a polyimide film tape.

[0037] Example 1.3 A preparation process of a polyimide film tape comprises the following steps: S1. Preparation of polyimide film: 2.5 kg of diamine (1.07 kg of p-phenylenediamine and 1.43 kg of 4,4'-diaminodiphenyl ether) was dissolved in 50 L of N,N-dimethylacetamide. Under nitrogen protection, the diamine was stirred until it was completely dissolved. Then, 0.3 kg of pyromellitic anhydride was added in 9 times. After each addition, the reaction was continued for 1 hour. The reaction temperature was 20°C. When the solid content in the system was greater than 15 wt%, a degassing treatment was performed to obtain a polyamic acid polymer. Subsequently, the prepared polyamic acid polymer was evenly coated on the glass using a CNC coating machine. Then, the glass was placed in an oven at 100°C for 0.5 hours and then transferred to a temperature oven. The film was placed in an oven at 150°C for 0.5h, transferred to an oven at 200°C for 0.5h, transferred to an oven at 250°C for 0.5h, transferred to an oven at 300°C for 0.5h, and finally transferred to an oven at 380°C for 0.5h. The film was taken out and placed in deionized water for demoulding after the temperature dropped to 25°C. The film was finally placed in an oven at 100°C for drying until the system had a constant weight. Finally, a polyimide film with a thickness of 25um and a surface roughness of R a is 1.27, and the dynamic water contact angle is 76.6°; S2, coating polymer emulsion: firstly, the temperature is raised to 360°C, and the surface of the polyimide film prepared in step S1 is coated with modified polytetrafluoroethylene emulsion by a CNC coating machine, and then dried to obtain a surface roughness R a A layer of coated tape with a g / L thickness of 1.47 is prepared, and then a modified polytetrafluoroethylene emulsion is coated for a second time using a CNC coating machine while the temperature remains unchanged. After coating, the temperature is increased to 400°C for melting, and after 3 hours, the tape is cooled and shaped, and dried to obtain a polyimide film tape.

[0038] Example 2.1 A preparation process of a polyimide film tape, which is different from that of Example 1.1 in that: in step S1, the polyimide film is further subjected to surface treatment, specifically: The polyimide film was completely immersed in a sodium hydroxide solution with a hydroxide ion concentration of 0.5 mol / L for alkaline treatment for 50 min, washed with deionized water, and then completely immersed in a hydrochloric acid solution with a hydrogen ion concentration of 0.12 mol / L for acid treatment for 8 min. After being taken out, it was washed with deionized water and dried to obtain a surface-treated polyimide film with a surface roughness R a is 1.60, and the dynamic water contact angle is 49.8°.

[0039] Example 2.2 A preparation process of a polyimide film tape, which is different from that of Example 1.1 in that: in step S1, the polyimide film is further subjected to surface treatment, specifically: The polyimide film was completely immersed in a sodium hydroxide solution with a hydroxide ion concentration of 0.05 mol / L for 60 minutes, washed with deionized water, and then completely immersed in a hydrochloric acid solution with a hydrogen ion concentration of 0.1 mol / L for 10 minutes. After being taken out, it was washed with deionized water and dried to obtain a surface-treated polyimide film with a surface roughness R a The dynamic water contact angle is 1.61 and 51.4°.

[0040] Example 2.3 A preparation process of a polyimide film tape, which is different from that of Example 1.1 in that: in step S1, the polyimide film is further subjected to surface treatment, specifically: The polyimide film was completely immersed in a sodium hydroxide solution with a hydroxide ion concentration of 0.3 mol / L for alkaline treatment for 55 min, washed with deionized water, and then completely immersed in a hydrochloric acid solution with a hydrogen ion concentration of 0.11 mol / L for acid treatment for 9 min. After being taken out, it was washed with deionized water and dried to obtain a surface-treated polyimide film with a surface roughness R a The dynamic water contact angle is 1.62 and 51.1°.

[0041] Example 2.4 A preparation process of a polyimide film tape, which is different from that of Example 1.1 in that: in step S1, the polyimide film is further subjected to surface treatment, specifically: The polyimide film was completely immersed in a sodium hydroxide solution with a hydroxide ion concentration of 0.02 mol / L for alkaline treatment for 50 min, washed with deionized water, and then completely immersed in a hydrochloric acid solution with a hydrogen ion concentration of 0.12 mol / L for acid treatment for 8 min. After being taken out, it was washed with deionized water and dried to obtain a surface-treated polyimide film with a surface roughness R a is 1.43, and the dynamic water contact angle is 67.1°.

[0042] Example 2.5 A preparation process of a polyimide film tape, which is different from that of Example 1.1 in that: in step S1, the polyimide film is further subjected to surface treatment, specifically: The polyimide film was completely immersed in a sodium hydroxide solution with a hydroxide ion concentration of 0.6 mol / L for alkaline treatment for 50 min, washed with deionized water, and then completely immersed in a hydrochloric acid solution with a hydrogen ion concentration of 0.12 mol / L for acid treatment for 8 min. After being taken out, it was washed with deionized water and dried to obtain a surface-treated polyimide film with a surface roughness R a is 1.46, and the dynamic water contact angle is 64.0°.

[0043] Example 3.1 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in the surface treatment of step S1, the hydroxide ion concentration of the sodium hydroxide solution is 0.1 mol / L, and the rest is the same as that of Example 2.1. The surface roughness R a The dynamic water contact angle is 1.61 and 64.0°.

[0044] Example 3.2 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in the surface treatment of step S1, the hydroxide ion concentration of the sodium hydroxide solution is 0.2 mol / L, and the rest is the same as that of Example 2.1. The surface roughness R a is 1.64, and the dynamic water contact angle is 42.1°.

[0045] Example 3.3 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in the surface treatment of step S1, the hydroxide ion concentration of the sodium hydroxide solution is 0.3 mol / L, and the rest is the same as that of Example 2.1. The surface roughness R a The dynamic water contact angle is 1.62 and 47.3°.

[0046] Example 3.4 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in the surface treatment of step S1, the hydroxide ion concentration of the sodium hydroxide solution is 0.4 mol / L, and the rest is the same as that of Example 2.1. The surface roughness R a The dynamic water contact angle is 1.60 and 51.0°.

[0047] Example 4.1 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in step S1, the diamines used are 0.75 kg p-phenylenediamine, 1 kg 4,4'-diaminodiphenyl ether and 0.75 kg 4,4'-diaminobenzanilide, and the rest are the same as those of Example 2.1.

[0048] Example 4.2 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in step S1, the diamines used are 0.75 kg p-phenylenediamine, 0.75 kg 4,4'-diaminodiphenyl ether and 1 kg 4,4'-diaminobenzanilide, and the rest are the same as those of Example 2.1.

[0049] Example 4.3 A preparation process of a polyimide film tape, which is different from that of Example 2.1 in that: in step S1, the diamines used are 0.75 kg p-phenylenediamine, 0.87 kg 4,4'-diaminodiphenyl ether and 0.88 kg 4,4'-diaminobenzanilide, and the rest are the same as those of Example 2.1.

[0050] Example 5.1 A preparation process for a polyimide film tape, which differs from Example 2.1 in that: in step S1, PDA-silane coupling agent-modified boron nitride is also added, specifically: 5.2 g of the PDA-silane coupling agent-modified boron nitride obtained in Preparation Example 1 is dispersed in 50 L of N,N-dimethylacetamide, and ultrasonically treated for 3 h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then mixed evenly with 2.5 kg of diamine (1.25 kg of p-phenylenediamine and 1.25 kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3 kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1 h after each addition, and the reaction temperature is 20°C. When the solid content in the system is greater than 15wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0051] Example 5.2 A preparation process for a polyimide film tape, which is different from that of Example 2.1 in that: in step S1, PDA-silane coupling agent-modified boron nitride is also added, specifically: 25g of the PDA-silane coupling agent-modified boron nitride obtained in Preparation Example 2 is dispersed in 50L N,N-dimethylacetamide, and ultrasonically treated for 4.5h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then mixed evenly with 2.5kg of diamine (1.25kg of p-phenylenediamine and 1.25kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1h after each addition, and the reaction temperature is 20°C. When the solid content in the system is greater than 15wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0052] Example 5.3 A preparation process for a polyimide film tape, which is different from that of Example 2.1 in that: in step S1, PDA-silane coupling agent-modified boron nitride is also added, specifically: 36.4 g of the PDA-silane coupling agent-modified boron nitride obtained in Preparation Example 3 is dispersed in 50 L of N,N-dimethylacetamide, and ultrasonically treated for 6 h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then mixed evenly with 2.5 kg of diamine (1.25 kg of p-phenylenediamine and 1.25 kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3 kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1 h after each addition, and the reaction temperature is 20°C. When the solid content in the system is greater than 15wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0053] Example 5.4 A preparation process for a polyimide film tape, which differs from Example 2.1 in that: in step S1, PDA-silane coupling agent-modified boron nitride is also added, specifically: 4g of PDA-silane coupling agent-modified boron nitride obtained in Preparation Example 1 is dispersed in 50L N,N-dimethylacetamide, and ultrasonically treated for 3h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then mixed evenly with 2.5kg of diamine (1.25kg of p-phenylenediamine and 1.25kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1h after each addition. The reaction temperature is 20°C, and when the solid content in the system is greater than 15wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0054] Example 5.5 A preparation process for a polyimide film tape, which differs from Example 2.1 in that: in step S1, PDA-silane coupling agent-modified boron nitride is also added, specifically: 40g of the PDA-silane coupling agent-modified boron nitride obtained in Preparation Example 1 is dispersed in 50L N,N-dimethylacetamide, and ultrasonically treated for 3h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then mixed evenly with 2.5kg of diamine (1.25kg of p-phenylenediamine and 1.25kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1h after each addition, and the reaction temperature is 20°C. When the solid content in the system is greater than 15wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0055] Examples 6.1-6.4 A preparation process of a polyimide film tape, which is different from Example 5.1 in that the added amounts of PDA-silane coupling agent modified boron nitride are 10g, 18g, 26g, and 34g, respectively, and the rest are the same as Example 5.1.

[0056] Example 7

[0057] A preparation process of a polyimide film tape, which is different from that of Example 4.1 in that: in step S1, PDA-silane coupling agent-modified boron nitride is also added, specifically: 26g of PDA-silane coupling agent-modified boron nitride prepared in Preparation Example 1 is dispersed in 50L N,N-dimethylacetamide, and ultrasonically treated for 3h to obtain a PDA-silane coupling agent-modified boron nitride dispersion, which is then mixed with 2.5kg of diamine (0.75kg of p-phenylenediamine, 1kg of 4,4'-diaminodiphenyl ether and 0.75kg of 4,4'-diaminobenzanilide) were mixed evenly, and under nitrogen protection, the diamine was stirred until it was completely dissolved. Pyromellitic anhydride was added in 9 portions, 0.3 kg of pyromellitic anhydride was added each time, and the reaction was carried out for 1 hour after each addition. The reaction temperature was 20°C. When the solid content in the system was greater than 15wt%, a degassing treatment was carried out to obtain a polyamic acid polymer, which was coated and dried to obtain a polyimide film.

[0058] Example 8.1 A preparation process for a polyimide film tape, which differs from Example 2.1 in that: in step S1, silane coupling agent-modified boron nitride is also added, specifically: 5.2 g of silane coupling agent-modified boron nitride obtained in Preparation Example 4 is dispersed in 50 L of N,N-dimethylacetamide, and ultrasonically treated for 3 h to obtain a silane coupling agent-modified boron nitride dispersion, which is then mixed evenly with 2.5 kg of diamine (1.25 kg of p-phenylenediamine and 1.25 kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3 kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1 h after each addition, and the reaction temperature is 20°C. When the solid content in the system is greater than 15wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0059] Example 8.2 A preparation process for a polyimide film tape, which differs from Example 2.1 in that: in step S1, PDA-modified boron nitride is also added, specifically: 5.2 g of the PDA-modified boron nitride obtained in Preparation Example 5 is dispersed in 50 L of N,N-dimethylacetamide, and ultrasonically treated for 3 h to obtain a PDA-modified boron nitride dispersion, which is then mixed evenly with 2.5 kg of diamine (1.25 kg of p-phenylenediamine and 1.25 kg of 4,4'-diaminodiphenyl ether), stirred under nitrogen protection until the diamine is completely dissolved, and pyromellitic acid dianhydride is added in 9 times, 0.3 kg of pyromellitic acid dianhydride is added each time, and the reaction is carried out for 1 h after each addition. The reaction temperature is 20°C, and when the solid content in the system is greater than 15 wt%, a degassing treatment is performed to obtain a polyamic acid polymer, which is coated and dried to obtain a polyimide film.

[0060] Comparative Example 1 The difference from Example 1.1 is that step S2 is a one-time coating, specifically: firstly, the temperature is raised to 410°C, and the surface of the polyimide film prepared in step S1 is coated with modified polytetrafluoroethylene emulsion by a CNC coating machine, and then dried to obtain a surface roughness R a The obtained tape is a 1.14-layer coated tape, which is cooled and shaped after 3 hours, and then dried to obtain a polyimide film tape.

[0061] Performance Testing 1. Film thickness test: a non-contact film thickness tester was used to measure the thickness of the polymer emulsion layer in step S2 of the embodiment and the comparative example; 2. Mechanical properties test: Take the polyimide film obtained in step S1 of the embodiment and the comparative example, cut it into 5 dumbbell-shaped specimens per group on a punching machine with the help of a standard cutter, install the specimens on the fixture of a universal tensile machine, and set the tensile rate to 10 mm / min for testing. After the test is completed, read the tensile strength and calculate the average value; 3. Bond strength test: Take the polyimide film tapes in the examples and comparative examples, cut them into a size of 150 mm × 10 mm, wipe the side coated with the polymer emulsion layer with benzene alcohol and white spunbond, then place a 150 mm × 10 mm × 1.0 mm copper sheet on the tape, overlap it neatly, and place it on the pressing surface of the sample preparation equipment at a temperature of 360 ± 2 ° C, and keep the pressure at 1 × 10 5Pa, press for 1.0min to obtain the sample, prepare 5 samples for standby in total for each group of embodiments or comparative examples; test the samples prepared above using a tensile testing machine with a range of 5-10kg and an accuracy of 0.02N, peel off the tape at both ends of the sample by hand for about 40mm, and then clamp the two peeled ends on the upper and lower clamps of a 50mm clamp respectively, and perform a 180° peeling test at a speed of 300mm / min, test 5 samples, and record the highest value, adhesion (N / 10mm) = tension × 10 / 10mm.

[0062] Table 1 Performance test table

[0063] Group Polyimide film tape thickness / um Tensile strength / MPa Example 1.1 15.2 179.2 Example 1.2 15.3 179.8 Example 1.3 15.3 179.7 Example 2.1 18.3 154.1 Example 2.2 18.0 154.7 Example 2.3 18.2 154.2 Example 2.4 16.5 160.7 Example 2.5 16.7 132.6 Example 3.1 18.4 154.7 Example 3.2 19.8 154.6 Example 3.3 18.2 154.4 Example 3.4 18.5 154.3 Example 4.1 18.3 182.3 Example 4.2 18.2 187.6 Example 4.3 18.4 184.9 Example 5.1 18.6 177.5 Example 5.2 18.7 177.4 Example 5.3 18.6 177.3 Example 5.4 18.6 162.6 Example 5.5 18.7 162.0 Example 6.1 18.7 178.4 Example 6.2 18.7 178.2 Example 6.3 18.7 182.9 Example 6.4 18.6 177.8 Example 7.1 18.6 165.6 Example 7.2 18.6 165.9 Comparative Example 1 9.7 175.4

[0064] Data Analysis: It can be seen from Table 1 that the surface roughness R of the polyimide films of Examples 1.1-1.3 after one coating is a The final thickness of the polymer emulsion layer is 15.2-15.3um, and the bonding force can reach 14.4-14.5N / 10mm, which proves that the application increases the temperature in a step-by-step manner to perform secondary coating. The surface roughness of the polymer emulsion after coating at the primary coating temperature of the application is relatively large, so the secondary coating can still effectively increase the coating layer thickness of the polymer emulsion, and the thickness of the polymer emulsion layer is relatively increased by at least 5um. The bonding force of the polyimide film tape and the firmness between the polyimide film tape and the electromagnetic wire are significantly improved, thereby improving the performance of the electromagnetic wire wrapping, and after wrapping, it can play an excellent role in waterproofing and electrical insulation of the electromagnetic wire; Embodiments 2.1-3.4 are different from Embodiment 1.1 in that, before the surface of the polyimide film is coated with the polymer emulsion, the surface is treated by immersing it in an alkaline solution and an acid solution, thereby introducing a large number of hydrophilic groups into the molecules on the surface of the polyimide film, thereby significantly improving the surface roughness, surface tension and wettability of the polyimide film, the dynamic water contact angle is not greater than 51.5°, and the surface roughness R a It can reach above 1.60, so the surface treated polyimide film can be fully wetted when coating the polymer emulsion, and the difficulty of coating the emulsion is greatly reduced. The thickness of the final polymer emulsion layer is greatly increased to 16.5-19.8um, and the bonding force can be increased to 14.9-16.2N / 10mm. Therefore, the surface treatment operation can significantly optimize the coating effect and increase the thickness of the polymer emulsion layer, thereby improving the bonding force of the polyimide film tape; Surface roughness R of the polyimide film of Example 2.4-2.5 aThe tensile strength of Example 2.5 also has obvious defects. In Examples 3.1-3.4, it can be clearly seen that the surface roughness of the polyimide film of Example 3.2 is the largest and the dynamic water contact angle is the smallest, which proves that the present application further optimizes the comprehensive performance of the polyimide film tape by strictly controlling the hydroxide ion concentration of the alkaline solution. If the hydroxide ion concentration is too large or too small, it will not have an effective surface treatment effect. The surface roughness, surface tension and wettability of the polyimide film are not improved enough. When the hydroxide ion concentration is too large, the surface layer of the polyimide film will be eroded by excessive alkaline solution, thereby exposing a large number of internal structures. After this part of the internal structure contacts the air, it will promote the initiation of cracks in the polyimide film tape, thereby damaging the tensile strength of the polyimide film. The tensile strength of the polyimide film of Examples 4.1-4.3 is significantly higher than that of Example 2.1, which proves that a certain amount of 4,4'-diaminobenzanilide is added to the diamine system composed of p-phenylenediamine and 4,4'-diaminodiphenyl ether in the present application, which partially replaces 4,4'-diaminodiphenyl ether and balances the ratio of rigid groups and flexible groups in the system, so that the final polyimide film has higher tensile strength; The tensile strength of the polyimide film of Examples 5.1-6.4 is significantly higher than that of Example 2.1, which proves that the present application adds PDA-silane coupling agent-modified boron nitride with high interface adhesion strength and high dispersibility to the raw materials used for the polyimide film, and utilizes the excellent mechanical strength and chemical stability of boron nitride, supplemented by the sufficient dispersion and adhesion effect of PDA-silane coupling agent-modified boron nitride, thereby significantly improving the overall tensile strength of the polyimide film. The final polyimide film has uniform internal components and high tensile strength, which is more than 15% higher than the tensile strength of the polyimide film to which PDA-silane coupling agent-modified boron nitride is not added; Moreover, the tensile strength of the polyimide film of Examples 5.4-5.5 is significantly lower than that of Example 5.1, while the tensile strength of the polyimide film of Example 6.3 is higher than that of other examples, which proves that the present application further optimizes the mechanical properties of the polyimide film by strictly controlling the addition amount of PDA-silane coupling agent-modified boron nitride. If the addition amount is too small, the reinforcement effect is insufficient. If the addition amount is too large, although the PDA-silane coupling agent-modified boron nitride will not form system defects and holes due to agglomeration, excessive addition will still cause a small part of the PDA-silane coupling agent-modified boron nitride particles to inevitably aggregate, and will still promote cracks in the polyimide film after being subjected to force, resulting in a decrease in the mechanical properties of the film. The difference between Example 7 and Example 2.1 is that a certain amount of 4,4'-diaminobenzanilide and PDA-silane coupling agent modified boron nitride are added at the same time, and the tensile strength of the final film is significantly improved, which proves that the application adds PDA-silane coupling agent modified boron nitride with high interface adhesion strength, high dispersibility and reinforcement effect while balancing the ratio of rigid groups and flexible groups in the system, which can further improve the tensile strength of the polyimide film, and its comprehensive improvement rate is much greater than the simple superposition of the improvement rate of adding a certain component alone; The tensile strength of the polyimide film of Examples 8.1-8.2 is significantly lower than that of Example 5.1, which proves that the PDA layer and the silane coupling agent can greatly enhance the interfacial adhesion strength of boron nitride and the diamine and dianhydride system and its dispersibility in the system, and significantly improve the overall tensile strength of the polyimide film; The thickness of the polymer emulsion layer in Comparative Example 1 is only 9.7um, and the bonding force is only 9.6N / 10mm, which proves that the temperature is increased in a step-by-step manner in this application for secondary coating. The surface roughness of the polymer emulsion after coating at the primary coating temperature of this application is relatively large, so the secondary coating can still effectively increase the coating layer thickness of the polymer emulsion. Compared with the traditional preparation process of single coating and molding, the thickness of the polymer emulsion layer can be relatively increased by more than 5um, and the bonding force can be increased by more than 4.8N / 10mm.

[0065] The embodiments of this specific implementation method are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. Therefore, all equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A process for preparing a polyimide film tape, comprising the following steps: S1, preparing a polyimide film, wherein the step of preparing the polyimide film comprises the step of preparing a polyamic acid polymer by reacting a diamine and a dibasic anhydride, S2, coating a polymer emulsion on the polyimide film, characterized in that: in the step S2, the coating is performed in two steps, specifically: First, the temperature is raised to the melting temperature of the polymer in the polymer emulsion, a coating is performed, and then dried to obtain the surface roughness R a The invention discloses a layer of coated tape with a thickness of >1.45, followed by secondary coating, after which the temperature is raised by 40-50°C for melting, and finally cooled to set and dried to obtain a polyimide film tape; the polymer emulsion is one or both of polyperfluoroethylene propylene emulsion and modified polytetrafluoroethylene emulsion.

2. The process for preparing a polyimide film tape according to claim 1, characterized in that: Before step S2, the polyimide film prepared in step S1 needs to be surface treated, and the specific steps are as follows: The polyimide film is completely immersed in an alkaline solution with a hydroxide ion concentration of 0.05-0.5 mol / L for alkaline treatment for 50-60 minutes, washed with water, and then completely immersed in an acid solution with a hydrogen ion concentration of 0.1-0.12 mol / L for acid treatment for 8-10 minutes, taken out, washed with water, and dried to obtain a surface-treated polyimide film.

3. The process for preparing a polyimide film tape according to claim 2, characterized in that: The hydroxide ion concentration is 0.2 mol / L.

4. The process for preparing a polyimide film tape according to claim 2, characterized in that: The diamine comprises p-phenylenediamine, 4,4'-diaminodiphenyl ether and 4,4'-diaminobenzanilide in a weight ratio of 3:(3-4):(3-4).

5. A process for preparing a polyimide film tape according to claim 2 or 4, characterized in that: In the step of preparing the polyamic acid polymer by reacting the diamine and the dibasic anhydride, a PDA-silane coupling agent-modified boron nitride is also added in an amount of 0.1-0.7wt% of the total amount of the dibasic anhydride and the diamine, specifically: The PDA-silane coupling agent modified boron nitride is dispersed in N,N-dimethylacetamide and ultrasonically treated for 3-6 hours to obtain a PDA-silane coupling agent modified boron nitride dispersion, which is then evenly mixed with a diamine, and finally a dibasic anhydride is added to react, coated, and dried to obtain a polyimide film.

6. The process for preparing a polyimide film tape according to claim 5, characterized in that: The amount of the PDA-silane coupling agent modified boron nitride is 0.5 wt % of the total amount of dibasic anhydride and diamine.

7. The process for preparing a polyimide film tape according to claim 5, characterized in that: The PDA-silane coupling agent modified boron nitride is prepared by the following method: The boron nitride is subjected to hydroxylation treatment, and then dispersed with a silane coupling agent in anhydrous ethanol, stirred for reaction, filtered, washed, and dried to obtain silane coupling agent-modified boron nitride. The silane coupling agent-modified boron nitride, dopamine and tromethamine are then dispersed in an ethanol aqueous solution, the pH is adjusted to 8.4-8.6, stirred at 75-85°C for 5.5-6h, filtered, washed, until the filtrate is colorless and neutral, and the solid obtained at this time is dried and ground to obtain PDA-silane coupling agent-modified boron nitride.

8. A polyimide film tape obtained by the preparation process of the polyimide film tape according to any one of claims 1 to 7, characterized in that: The layer thickness of the polymer emulsion of the polyimide film tape is not less than 15 um.

Citation Information

Patent Citations

  • Emulsion for polyimide film fluorine-containing coating

    CN103897514A

  • Polyimide composite film for special cable and preparation method thereof

    CN113831570A

  • Preparation method of multi-layer coated low-dielectric-constant composite polyimide film

    CN116217995A

  • Silicone rubber filling mud and preparation method thereof

    CN118931188A

  • Production and apparatus for polyimide-fluorine 46 adhesive tape

    CN1746248A